(untitled) (Research, Society and Development, 2022)
The main objective of this research was to analyze the methods of evaluation and monitoring of health in public schools for elementary school children. The methodological strategy is bibliographic and exploratory. Ten articles published from 2010 to 2021 were analyzed, all selected from the SciELO and LILACS database resulting from the descriptors: Health, Anthropometrics, Schools, Elementary School. Articles focused on assessment methods that are commonly used and methods that can be put into practice in public schools were analyzed. Among the main results found, it was possible to observe that BMI is a method most used in schools, but other methods such as WHR, WHR and WC, for example, would also be very effective for the evaluation and monitoring of the health of schoolchildren, in addition to the associations of these methods that in the research carried out are promising. Therefore, the association of assessment methods could be easily adopted in schools, due to the simplicity of the material used. In addition, this study also identified the scarcity of research focused on fundamental II, mainly referring to assessment methods in schoolchildren in this age group.